Improving friction yarn qualities for its use in foundation garments: Part 2 - Singh, K. V. P. (2014)
[Excerpt] An attempt has been made to develop DREF III friction spun yarn after structural modifications with an objective to analyze its feasibility for apparel end use by diagnosing its quantified reduction in harshness [1]. An independent study is carried out to develop a regression model, for simultaneous optimization of the desirability of physiological comfort and handle related properties of a knitted fabric, made up of the modified friction spun yarn, with predefined constraints in desired atmospheric conditions for specific end-use and comparing it with knitted fabric made up of conventional friction spun yarn named as ‘Reference fabric’ [2][3]. To optimize the desirability of value added garment, response surface methodology is used as a tool to develop a mathematical model [4]. In this work, ‘Physiological Control System’ (PCS) of both comfort & handle is being upgraded to ‘Engineering Control System’ (ECS) by conversion of conceptual model to a mathematical model [5]. Optimizing the fabric handle properties is based on the basic concept of neuroscience; artificial neuron model; physiological control system & engineering control system. Re-optimization of both comfort and handle by reverse engineering process is done to identify the best sample with maximum overall desirability termed as an ‘Ideal fabric’ to achieve value added quality garment. ‘Ideal fabric’ is identified as per the synergistic target & goal i.e. which satisfies & saddles both the parameters of comfort and handle in a compromise zone [6]. (...)